The relationship between human resource practices and employee retention - Abu, S.E. Mohammad Shariff (2015)
Employee retention is one of the challenges facing many organizations today. Realising human resource as the most critical asset, retaining good employees is vital for organizations striving to gain competitive advantage. Organizations practice various human resource management (HRM) techniques for employee retention. This study was conducted to examine the relationship between HRM practices, namely compensation and benefits, training and development, and working environment, with employee retention. Data was collected from 1 10 respondents from an automotive parts manufacturer located in Perak. The findings indicated positive and significant but low relationships between compensation and benefits, training and development, and working environment with employee retention. The three HRM practices in this study explained only 22.8% of employee retention. It is hoped that this study will help both academics and those managing human resource to realize, understand and see the influence of HRM practices, beyond the three which were included in this study, on employee retention. Future research should include a larger number of organizations in other industries or sectors